Ces corps qui comptent : de la matérialité et des limites discursives du sexe - Butler, Judith (Éditions Amsterdam, 2009)
Traduction de Bodies That Matter, (1993) La prise en compte de la matérialité des corps n’implique pas la saisie d’une réalité pure, naturelle, derrière le genre : si le sexe est un présupposé nécessaire du genre, nous n’aurons jamais accès au réel du sexe qu’à travers nos schèmes culturels. Le sexe, comme le genre, est une norme culturelle, qui régit la matérialité des corps. Il importe donc de souligner que le concept de matière a une histoire, où sont sédimentés les discours sur la différence sexuelle. En outre, si certains corps (par exemple blancs, mâles et hétérosexuels) sont valorisés par la norme, d’autres (par exemple lesbiens ou non blancs) sont produits comme abjects, rejetés dans un dehors invivable. À travers une reprise critique du concept foucaldien de « contrainte productive », Judith Butler s’efforce, loin de tout volontarisme, de ressaisir la façon dont ces corps peuvent défaire les normes qui les constituent et devenir le lieu d’une puissance d’agir transformatrice. Ce livre, où l’épistémologie se mêle à la politique, constitue un jalon des études de genre et l’un des ouvrages majeurs de son auteure.
Donné en lecture a cours POL4212, « Critically Queer », pp 225-244.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; art contemporain; corps; cours; culture; discipline; fem1000; genre; hétérosexisme; identités LGBTQIA2+; lit4700; maternité; philosophie; pol4212; politique; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe; soc2014; systèmes d'oppressions; thématiques; épistémologie; épistémologie queer; états-unis; études culturelles

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (Rowman & Littlefield, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Section: xx, 236 pages
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques